2017
DOI: 10.1177/1538574417739090
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stent Can Be the Treatment of Choice for Spontaneous Iliac Vein Rupture: A Case Report

Abstract: Endovascular repair is an effective and safe treatment. Compared with open laparotomy and primary suture, stent leads to fewer complications and a lower mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…We found a total of 53 cases mostly consisting of isolated case reports with Google search. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Jiang et al reported a series of 9 J o u r n a l P r e -p r o o f cases although in 4 of these patients, there were no imaging studies or operative findings to confirm iliac vein rupture .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a total of 53 cases mostly consisting of isolated case reports with Google search. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Jiang et al reported a series of 9 J o u r n a l P r e -p r o o f cases although in 4 of these patients, there were no imaging studies or operative findings to confirm iliac vein rupture .…”
Section: Discussionmentioning
confidence: 99%
“…We found a total of 53 cases, which were mostly from isolated case reports, using a Google search. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Jiang et al 5 reported a series of nine patients, although for four of these patients, no imaging studies or operative findings to confirm iliac vein rupture were reported. Of these 53 cases, 14 patients died, for a mortality rate of 26.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, covered stents were employed (Adams MK et al 2012 ). In one case, external iliac vein rupture was repaired with an endovascular stent and open laparotomy for abdominal decompression (Chen YC et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is needed in the majority of the cases. So far, only 2 patients received endovascular treatment [7 , 8] . This disease has never been imaged in a study before.…”
Section: Introductionmentioning
confidence: 99%